Revitalisation and Revival of Traditional Musical Instruments in Poland in the Context of Music Contests - Nowak, Tomasz (Interdisciplinary Studies in Musicology, 2022)
This article is devoted to the issue of revitalisation and revival of traditional musi- cal instruments in Poland in the context of music competitions. Research on revival activities in Poland is rare, as is research on the phenomenon of traditional music competitions. Meanwhile, over the last nine decades, traditional music competitions have become the main environment for the public presentation of traditional music and stimulating the revival and revitalisation of indi- vidual musical phenomena. In this area, I have been conducting my own participant observations and archival research for over two decades. I understand the revival phenomenon itself and the activities that constitute it after Caroline Bithell and Juniper Hill (2013). The distinction between the terms revitalisation and revival is based on that made by Ingrid Åkesson (2006) and Ulrich Morgenstern (2019). In the text I discuss the issue of revitalisation of the Podhale bagpipes and the revival of the hurdy-gurdy. I also show that the phenomenon of the revival of musical tradi- tion is accompanied by processes of depreciation of the role, importance or presence of other instruments, such as the accordion or clarinet. I also show the important role of the activism of leading figures among both researchers and lovers of traditional music, as well as musicians and instrument builders.